CCB Release Impact on Indonesia’s Bank Lending: A Difference-in-Differences Approach - Suci, Sang Tyas; Gitaharie, Beta Yulianita (UI Scholars Hub, 2026)
This study investigates the impact of Indonesia’s Capital Conservation Buffer (CCB) release on loan growth during the COVID-19 recession. Using a Difference-in-Differences (DiD) approach and bank-level data from 2019:Q1 to 2022:Q2, it analyzes how regulatory capital relief affected lending. The results indicate that the regulation was an effective countercyclical tool to increase loan growth, particularly among less-capitalized banks. The research contributes to the limited empirical evidence on capital buffer policies in emerging markets by examining the effectiveness of temporary capital relief in crisis contexts. We suggest future research on the buffer reimposition and exploring its implications for post-crisis lending behavior.